2015
DOI: 10.1007/s00198-015-3213-z
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic antidepressant use and the risk of fracture: a population-based nested case–control study

Abstract: Current use of SSRI/SNRI is associated with an increased risk of all caused fractures. Additionally, the co-morbidity, especially osteoporosis and a history of falling, plays an important role in the risk of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The studies we found were published between 1998 and 2016, with 11 studies since 2013 . Two studies were reported across multiple articles and each was treated as a single distinct study: Vestergaard et al and Souverein et al One study reported results from both a cohort and a nested case‐control analysis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations